2007
DOI: 10.1177/008124630703700307
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Research on Positive Psychology in South Africa

Abstract: The paradigm of positive psychology was publicly launched by Martin Seligman in his Presidential Address to the American Psychology Association in 1998. Since then, the scientific study of optimal human functioning gained new momentum. This article provides an overview of research on positive psychology in South Africa. The article explores general trends and the main developments in the field, internationally as well as nationally. South African research in the paradigm of positive psychology was categorised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Job or work stress, job burnout and attitudinal variables related to downsizing, harassment, work-family pressures, outsourcing violation of psychological contracts and job insecurity are also important research themes . South-African based research revealed a notable increase in well-being studies after 2000 (Coetzee & Viviers, 2007;Moyo, 2012;. Moyo (2012) also indicates employee wellness as an important current research issue for business and practice.…”
Section: Scopementioning
confidence: 99%
“…Job or work stress, job burnout and attitudinal variables related to downsizing, harassment, work-family pressures, outsourcing violation of psychological contracts and job insecurity are also important research themes . South-African based research revealed a notable increase in well-being studies after 2000 (Coetzee & Viviers, 2007;Moyo, 2012;. Moyo (2012) also indicates employee wellness as an important current research issue for business and practice.…”
Section: Scopementioning
confidence: 99%
“…The scientific study of optimal living has a research record spanning over 36 years and includes numerous approaches, theories and concepts, currently regarded as constituting the field of positive psychology (Coetzee & Viviers, 2007). As a result, various psychological wellness constructs have evolved, supporting the view that psychological wellness is a multidimensional phenomenon with optimal living at its core (Gropp, Geldenhuys & Visser, 2007).…”
Section: Psychological Wellness and Sense Of Coherencementioning
confidence: 99%
“…Even in research works carried out in South Africa (see Coetzee and Viviers 2007 ;Eloff 2008 ) ATR gets no mention. Worthy of mention here, though, is the work by Biswas-Diener ( 2006 ) that evaluates the existence, importance and desirability of character strengths across cultures.…”
Section: Religious Traditions and The Character Strengthsmentioning
confidence: 99%